2004
DOI: 10.1007/s00540-003-0222-4
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring magnesium to guide magnesium therapy for heart surgery

Abstract: ionized Mg (iMg). Measurement of TMg requires the isolation of plasma (centrifugation of blood sample) or serum (clotting and centrifugation of blood sample). Measurement is made by atomic absorption spectrophotometry or colorimetry. Reference values for plasma and serum TMg typically range from 0.66 to 1.07 mmol·l Ϫ1 . There is virtually no correlation between plasma/serum TMg and intracellular TMg.Ionized magnesium (iMg ϭ Mg 2ϩ ) represents the activity of unbound Mg in whole blood plasma, plasma, and/or ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Magnesium deficiency presents among about 71% of patients who underwent Cardiopulmonary bypass (CPB) [ 5 ]. In many studies intraoperative addition of the magnesium sulfate was beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium deficiency presents among about 71% of patients who underwent Cardiopulmonary bypass (CPB) [ 5 ]. In many studies intraoperative addition of the magnesium sulfate was beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Cobas® (Roche), Advia® (Siemens), Architect® (Abbott) and Synchron® (Beckman Coulter), they are not easily applied to POC testing applications, e.g., testing in ED, OR, ICU and ambulance environments. Recent clinical studies [3] demonstrated the association of hypomagnesemia and mortality rates [6] in ICU patients experiencing hemodialysis [18], type 2 diabetes [19], cardiovascular diseases [20], cardiovascular deaths, and medical surgical intensive care [21]. Monitoring and controlling iMg may be more relevant in patient care than TMg, especially when an abnormal protein concentration can be expected, as is often seen for critically ill patients [22,23].…”
Section: Img Testing For Point Of Care Diagnosticsmentioning
confidence: 99%
“…Six to sixty-fi ve percent of all hospitalized patients exhibit low serum Mg; patients with numerous cardiovascular disorders associated with atherogenesis demonstrate the most profound defi cits in body Mg. 3,[10][11][12][13][14][15][16][17][18][19][20][21] 22,23 Because the levels of anions can vary signifi cantly in pathological states, and in view of the role apparently played by Mg in cellular homeostasis (Table 19.2), it is desirable to directly measure free Mg 2+ in blood 24 and other body fl uids. With this aim in mind, Mg 2+ -sensitive electrodes have been designed to obtain these measurements in the presence of potential cationic interferences.…”
Section: Magnesium Depletion From the Body Is Commonmentioning
confidence: 99%